Dampak Pengembangan Kebiajakan Anugerah Desa Wisata Indonesia (ADWI) terhadap Pertumbuhan Industri Pariwisata dan Perekonomian Masyarakat Lokal - Putra, Fabio Esa (JURNAL NASIONAL PARIWISATA, 2023)
Tourism is an important sector for the Indonesian economy, and the country is well-equipped to make tourism a leading industry that can compete on the global stage. However, the Covid-19 pandemic has had a significant impact on the tourism industry in Indonesia. To revive the industry and attract more tourists, the Ministry of Tourism created Anugrah Desa Wisata Indonesia (ADWI), an award given to outstanding tourist villages that meet certain assessment criteria. This initiative is expected to boost tourism and promote economic growth in local communities.This research aims to examine the impact of the ADWI policy on the development of the tourism industry and the local economy. The study uses a descriptive qualitative approach with data collected from interviews, observations, and other supporting documents. The results indicate that the ADWI policy has had a significant impact on the tourism industry, as evidenced by the development of supporting infrastructure, an increase in the number of visitors, and income generated from tourist attractions. However, while there have been more business and job opportunities, the impact on the local economy has not been significant.